Integration of Islamic Values in POACE Practice: An Effort to Islamize Education Based on Islamic Education Philosophy - Sayyid Muhammad Indallah; Muhammad Faqih Nidzom; Firda Inayah; Imroatul Istiqomah; Muhammad Iman Kurniawan; Hendro Risbiyantoro (NAJAHA, 2025)
This study analyzes the integration of Islamic values into the POACE (Planning, Organizing, Actuating, Controlling, Evaluating) management model as an effort to operationalize the Islamization of education based on Islamic education philosophy. It aims to develop an operational framework that synthesizes modern management principles with Islamic ethics to create holistic and spiritually-grounded educational practices. Employing a descriptive-analytical method, the research collected data through literature review, document analysis, and case studies of educational institutions implementing Islamic value-based POACE. The analysis reveals that each stage of POACE can be effectively integrated with core Islamic values: planning founded on sacred intention (niyyah) and tawhid, organizing that upholds justice (‘adl) and trust (amanah), actuating that embodies righteous action (amal saleh) and sincerity (ikhlas), controlling infused with conscientious oversight (muraqabah), and evaluating grounded in fairness (qist) and compassion (rahmah). The discussion indicates that this synthesis transforms POACE from a neutral administrative tool into a value-laden framework for educational leadership, effectively bridging the gap between Islamic philosophical ideals and contemporary managerial demands. The study concludes that integrating Islamic values into POACE provides a systematic approach for cultivating graduates who are not only academically competent but also morally upright and socially responsible. The implications suggest this model can be adopted in curriculum development and teacher training for Islamic religious education. Future research is recommended to test the model's efficacy across diverse institutional contexts and evaluate its long-term impact on student character formation.